Use of a single intramuscular injection of a synthetic hormone analogue,ovupin for commercial carp seed production in Bangladesh - Md. Rashedul Kabir Mondol; Sharmin Jaman Provhat; Md. Arif Hossain (Universiti Kebangsaan Malaysia, 2014)
A study was conducted to investigate the possibility of employing a single intramuscular injection of a synthetic hormone analogue, ovupin on the induced breeding of two major carps, viz. rohu (Labeo rohita), mrigala (Cirrhinus mrigala) and an endangered minor carp, bata (Labeo bata). Three breeding trials of each species were performed. In case of major carp, the females were injected with single dose of ovupin solution at a rate of 0.5 mL kg-1 body weight, while the minor carp received ovupin solution at a dose of 0.3 mL kg-1 body weight, whereas males received extracted PG hormone at a dose of 2 and 1.5 mg kg-1 body weight for major carps and minor carp, respectively. All the three species were successfully bred using ovupin through a single injection. In case of major carps, the latent period was 9-10 h while 12-14 h for minor carp. The breeding response of females was 100% in major carps, whereas it was approximately 90% in minor carp. Fertilization rate varied between 87.07 and 89.94% for the major carps and between 87.6 and 89.9% for minor carps. Major carps showed higher hatching rates (77.21 to 80.19%) than minor carp (64.9 to 66.56%). The present study indicated that ovupin could be effective as alternative of PG in carp’s breeding in Bangladesh.